2015
DOI: 10.1021/ja512029x
|View full text |Cite
|
Sign up to set email alerts
|

Pd(II)-Catalyzed Enantioselective Synthesis of P-Stereogenic Phosphinamides via Desymmetric C–H Arylation

Abstract: We present the enantioselective synthesis of P-stereogenic phosphinamides through Pd-catalyzed desymmetric ortho C-H arylation of diarylphosphinamides with boronic esters. The method represents the first example of the synthesis of P-stereogenic phosphorus compounds via the desymmetric C-H functionalization strategy. The reaction proceeded efficiently with a wide array of reaction partners to afford the P-stereogenic phosphinamides in up to 74% yield and 98% ee. The efficiency was further demonstrated by gram … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
78
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 207 publications
(81 citation statements)
references
References 54 publications
1
78
0
2
Order By: Relevance
“…It is well known that chiral phosphorus compounds play important roles as ligands or organocatalysts in asymmetric synthesis [73][74][75][76]. In 2015, Han group reported the asymmetric syntheses of traditionally inaccessible P-stereogenic phosphinamides via Pd-catalyzed enantioselective C(sp 2 )-H functionalization (Scheme 18) [77]. It is well known that chiral phosphorus compounds play important roles as ligands or organocatalysts in asymmetric synthesis [73][74][75][76].…”
Section: Scheme 14mentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that chiral phosphorus compounds play important roles as ligands or organocatalysts in asymmetric synthesis [73][74][75][76]. In 2015, Han group reported the asymmetric syntheses of traditionally inaccessible P-stereogenic phosphinamides via Pd-catalyzed enantioselective C(sp 2 )-H functionalization (Scheme 18) [77]. It is well known that chiral phosphorus compounds play important roles as ligands or organocatalysts in asymmetric synthesis [73][74][75][76].…”
Section: Scheme 14mentioning
confidence: 99%
“…Scheme 18. Enantioselective synthesis of P-stereogenic phosphinamides via asymmetric C-H arylation [77].…”
Section: Scheme 19mentioning
confidence: 99%
“…63 In early 2015, we reported a Pd (II) to Pd (0) catalytic cycle for intermolecular asymmetric C-H arylation of phosphinamides with boronic esters using readily available amino acids as chiral ligands. 64 (Scheme 1, Eq. (1)).…”
Section: Introductionmentioning
confidence: 99%
“…For the asymmetric C-H functionalization of phosphinamides, although a highly enantioselective arylation with pinacolborates has been accomplished, 64 an earlier study in our lab showed that the reaction was less effective for boronic acid nucleophiles. This is unsurprising since it was observed in Suzuki-Miyaura cross-coupling that the four major classes of arylboron-based nucleophiles, including boronic acids, trifluoroborates, neopentylglycolborates, and pinacolborates often exhibit markedly different reactivities even for the same coupling partner, 69 i.e., the optimized reaction conditions for one of the four nucleophiles are not necessarily applicable to others and vice versa.…”
Section: Introductionmentioning
confidence: 99%
“…As this mild C-H functionalization reaction generated stereogenic phosphinamides, the same group subsequently disclosed a closely related protocol for an enantioselective transformation (Scheme 28). 68 Inspired by Yu's work, an MPAA was selected as a chiral ligand. After an extensive optimization of the reaction conditions, including investigations into the organoboron reaction partner, oxidant, base and solvent, an efficient catalytic system was developed.…”
mentioning
confidence: 99%